Psychometric properties of the Polish version of the Generalized Anxiety Disorder Scale (GAD-7) in a non-clinical sample of employees during pandemic crisis - Beata Aleksandra Basińska; Zuzanna Kwissa-Gajewska (International Journal of Occupational Medicine and Environmental Health, 2023)
Objectives The COVID-19 outbreak is an example of a crisis that triggered an increase in generalized anxiety disorder. The study aims to validate the Polish version of the Generalized Anxiety Disorder 7-item scale (GAD-7) by Spitzer et al. among a non-clinical sample of employees and examine the invariance depending on the gender and age of working adults.